ChemInform Abstract: Development of Pseudorotaxanes and Rotaxanes: From Synthesis to Stimuli‐Responsive Motions to Applications. Issue 39 (September 2015) - Xue, Min; Yang, Yong; Chi, Xiaodong; Yan, Xuzhou; Huang, Feihe
Abstract Review: 681 refs.